Communicating health: media framing of ebola outbreak in Nigerian newspapers - Adekunle, Adelakun Lateef; Hamedi M. Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Mass media cannot cure virus but can cure its spread. Framing of news stories in the Nigerian media (newspapers) is much more influenced by the economic motive of the journalists; picking news angle that arouses readers’ interests in order to sell more copies in the keen competitive media market. The 2014 Ebola outbreak is a litmus test of how Nigerian media framed health issues, which depict the news perspective most interest to them. Through content analysis of two daily newspapers reports of Ebola during the outbreak in Nigeria, this study established the framing patterns employed while reporting as well as the preponderant frames used. The outcome is used to justify the priority upheld between the competing newspapers interests to sell and the media social responsibility towards containing the outbreak. The much capitalisation on treatment/containment frame portrayed the newspapers purposive interest to free the society of the outbreak, a reflection of its social responsibility role. The priority, which pose no threat on the professionalism of journalism was not only much appraised but also recommended for all media involvement in crisis reports.